2019
DOI: 10.1136/bmjoq-2019-000763
|View full text |Cite
|
Sign up to set email alerts
|

Severe illness getting noticed sooner – SIGNS-for-Kids: developing an illness recognition tool to connect home and hospital

Abstract: BackgroundDelays to definitive treatment for time-sensitive acute paediatric illnesses continue to be a cause of death and disability in the Canadian healthcare system. Our aim was to develop the SIGNS-for-Kids illness recognition tool to empower parents and other community caregivers to recognise the signs and symptoms of severe illness in infants and children. The goal of the tool is improved detection and reduced time to treatment of acute conditions that require emergent medical attention.MethodsA single-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…This knowledge often allows them to recognise well in advance when their child is showing signs and symptoms of illness (Rennick et al, 2019; Spratling & Lee, 2020). The warning signs and symptoms of clinical deterioration that prompt parents of children with MC to intervene are common to children with acute conditions (Gaskin et al, 2018; Gilleland et al, 2019; Rudd et al, 2020). However, we found that parents of children with MC with less experience rely primarily on vital signs monitoring while more expert parents are alerted by their child's behaviour and their own intuition to identify evolving clinical deterioration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This knowledge often allows them to recognise well in advance when their child is showing signs and symptoms of illness (Rennick et al, 2019; Spratling & Lee, 2020). The warning signs and symptoms of clinical deterioration that prompt parents of children with MC to intervene are common to children with acute conditions (Gaskin et al, 2018; Gilleland et al, 2019; Rudd et al, 2020). However, we found that parents of children with MC with less experience rely primarily on vital signs monitoring while more expert parents are alerted by their child's behaviour and their own intuition to identify evolving clinical deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…This knowledge often allows them to recognise well in advance when their child is showing signs and symptoms of illness (Rennick et al, 2019;Spratling & Lee, 2020). The warning signs and symptoms of clinical deterioration that prompt parents of children with MC to intervene are common to children with acute conditions (Gaskin et al, 2018;Gilleland et al, 2019;Rudd et al, 2020).…”
Section: Category 3-parents' Care Monitoringmentioning
confidence: 99%
“…With increased vaccines, better maternity care and societal hygiene, the current health situation has changed considerably in the past three decades. In addition, there is more evidence of the important indicators of severe illness in infants which has been translated into tools such as the PArents’ Trigger Tool for Children with Medical Complexity (PAT-CMC) 10 and the SIGNS-for-Kids illness recognition tool 11 to guide parents, carers and clinicians. Creating resources to empower parents and carers to detect serious illness in young infants therefore necessitates a review of current clinical guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Timely identification of severe illness provides opportunity to prevent clinical deterioration and reduce morbidity and mortality 1–4. An expert panel consisting of parents and multidisciplinary providers created the Severe Illness Getting Noticed Sooner (SIGNS)-for-Kids as a public health tool to help caregivers identify and articulate the manifestations of severe illness in children 5. The tool was created during a consensus development workshop to incorporate expert opinion and previously published symptom checklists of severe illness 6 7.…”
Section: Introductionmentioning
confidence: 99%